DETERMINATION OF UPPER LIMIT FOR INVESTMENT IN CHERRY PLANTATION ESTABLISHMENT - Milić, Dušan; Sredojević, Zorica; Jeločnik, Marko (Economics of Agriculture, 2008)
Investing in establishment of cherry plantation has many risks. To avoid that, or in some extent diminish the financial risk, prior to plantation it is necessary to correctly estimate the financial investments for certain growth years, as well as, expected yields during planned period of plantation exploitation. Based on reliable estimation it can be answered the following question: Which is the largest amount of financial assets, which could be invested in cherry plantation, whose exploitation during its life, as means with biological characteristics, can give positive financial effect? By determination of yield value for plantation on area of 20 hectares, this paper work is trying to determine upper limit of financial assets invested in plantation, as one way for estimation and avoidance of financial risk.